Incidence trends of early-onset breast cancer by lifestyle risk factors - Jasmiina Rantala; Karri Seppä; Johan Eriksson; Sirpa Heinävaara; Tommi Härkänen; Pekka Jousilahti; Paul Knekt; Satu Männistö; Ossi Rahkonen; Nea Malila; Eetu Mäkinen; Heidi Ryynänen; et al. (BMC Cancer, 2025)
Abstract Background The incidence of early-onset breast cancer (< 50 years) has been increasing over the past decades with the role of modifiable, lifestyle-related risk factors remaining mostly unidentified. Methods To investigate the role of key lifestyle factors in the incidence trends of early-onset breast cancer (EOBC), we pooled data from six health studies in Finland in 1972–2015 and combined them with breast cancer data from the Finnish Cancer Registry. The cohort consisted of 56,253 women with 397 EOBCs. The effects of risk factors (hazard ratios) on EOBC and average annual percent change (AAPC) of incidence were estimated using Poisson regression models. Results The highest annual increase in age-standardized incidence was observed among women aged 40–49 who were overweight (AAPC 4.0%, 95% CI 0.5–7.7%), currently smoking (AAPC 3.3%, 95% CI 0.1–6.6%) or moderately physically active (AAPC 2.9%, 95% CI 0.3–5.6%). Conclusions The increase in early-onset breast cancer incidence was highest among women aged 40–49 who were overweight, currently smoking, or moderately physically active, while no change by risk factors was found in women under 40 years of age. Our findings suggest a different type of cancer process in young adults and highlight the importance of lifestyle risk factors in the incidence of EOBC.